FEMINISME RADIKAL DALAM NOVEL PENGAKUAN EKS PARASIT LAJANG KARYA AYU UTAMI - Andriani Ningsih; Andaru Ratnasari (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2021)
Radical is the oppression of women that occurs due to the patriarchal system. The female body is the main object of oppression by male power. In the novel Pengakuan Eks Parasit Lajang by Ayu Utami. Reveals the life expreriended by women in justice and violence, which leads to a corner of fate, such as character A who decides to give up her virginity at the age of twenty. At the same time removing the concept of virginity which he thought was unfair. The core purpose of this research is to increase the position and degree of women to be equal or equal to the position and rank of men. The strugge and the effort to achieve this goal involves a variety of ways. On of the ways is to obtain the same rights and opportunities as men. In the connection with this, the term women's discussion movement emerged. Another way is to free women form the ties of the domestic environment or the family an house hold environment. The novel Pengakuan Eks Parasit Lajang by Ayu Utami, shows the struggle of female figures to break through the patriarchal system which is considered to be the root of gender injustice that plases women with a patriarchal system. This was done to show the existance of a women movement to end oppression from the patriarchal system. One of the feminist ideas in the novel Pengakuan Eks Parasit Lajang show the similarity between the novel Pengakuan Eks Parasit Lajang and the radical feminism repsented by the character in the novel Pengakuan Eks Parasit Lajang.